+0  
 
0
170
2
avatar

(-1)^n-(1)^n=

Guest Mar 8, 2017
 #1
avatar+19653 
+5

(-1)^n-(1)^n=

 

\((-1)^n-(1)^n= (-1)^n - 1\)

 

laugh

heureka  Mar 8, 2017
 #2
avatar+92806 
0

Thanks Heureka,

 

I'll go one step further:

\((-1)^n-(1)^n= (-1)^n - 1 \)

 

If n is even then this is      1-1=0

if n is odd then this is        -1-1=-2

Melody  Mar 8, 2017

8 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.